Beyond Automated Feedback: Indonesian Educators’ Reflections on Deepseek AI’s Role in Fostering Metacognition - Ahmad, Ardiansyah (Universitas Terbuka, 2025)
The integration of artificial intelligence (AI) tools in education has generated considerable interest due to their potential to enhance formative assessment, metacognition, and self-regulated learning. However, in resource-constrained settings, cost and infrastructural barriers often hinder widespread AI adoption. This qualitative study examines Indonesian educators’ perceptions of Deepseek AI, a free AI platform offering functionalities similar to more commercially dominant tools. Through semi-structured interviews with 14 teachers and lecturers in South Sulawesi, the study explores how Deepseek AI supports formative assessment, fosters metacognitive skills, and aligns (or misaligns) with local cultural and infrastructural contexts. Thematic analysis revealed that Deepseek AI’s real-time feedback, adaptive pathways, and automated grading significantly reduce teacher workload and enhance student engagement. Participants also noted improvements in learners’ metacognitive reflection, with AI-generated prompts prompting students to examine their problem-solving strategies. Nonetheless, rural educators reported connectivity gaps that delayed feedback and limited the tool’s effectiveness. Concerns over cultural mismatch in AI-generated materials were also prominent, highlighting the need for localized content that resonates with Indonesian norms and values. While ethical considerations such as data privacy were mentioned, most educators stressed the urgency of training and policy support—particularly government-led investments in rural broadband and professional development programs. Overall, the findings underscore both the promise and complexity of integrating AI in low-resource educational settings. Deepseek AI can catalyze more efficient, learner-centered pedagogies if stakeholders address infrastructural inequities, cultivate teacher readiness, and ensure cultural and ethical alignment. These insights inform policymakers, EdTech developers, and educators seeking equitable AI solutions that optimize student learning outcomes. Keywords: Artificial Intelligence in Education, Formative Assessment, Metacognition, Teacher Perceptions, Indonesia